A new approach for the laboratory culture of the fathead minnow, Pimephales promelas. (5th November 2013) - Gordon, Denise A.; Smith, Mark E.; Wratschko, Melissa; Agard, David; Holden, Lisa; Wilcox, Steve; Lazorchak, James M.
Abstract Fathead minnows are routinely cultured for use in aquatic toxicology studies. A new mass culture system described in the present study consisted of 6 stainless steel tanks, each containing 68 fish and 20 spawning substrates. Spawning results are compared with a previous system of 22 individual glass aquaria, which contained 16 fish and 4 spawning substrates per tank. During a 19‐mo period, the new system produced an average of 4105 eggs/d, compared with an average of 2465 eggs/d with the previous system. Labor and maintenance were reduced with the new system. The stainless steel tanks eliminated aquaria glass breakage, and daily water use was reduced by 45%. Analysis of reference toxicant data from fish cultured using both systems indicated no change in the sensitivity of the test animals. Analyses of 2009 egg production data determined that a 6:1 to 7:1 female to male ratio had a significantly positive impact on egg production levels and that 6‐mo‐old breeding stock should be introduced to the spawning tanks in mid‐spring for optimal egg production during the rest of the year. Implementing a stainless steel mass culture system significantly increased efficiency of egg production; reduced turnaround delay of mature animal availability for toxicity and molecular testing; and reduced labor time, costs, and inherent safety hazards, compared with glass aquaria systems. Environ Toxicol Chem 2014;33:126–133. © 2013 SETAC